Examining the etiologic association between toxoplasma gondii and schizophrenia: A comprehensive meta-analysis approach - Deblois, Bea Ysabelle K. (Animo Repository, 2023)
The obligate intracellular protozoa T. gondii has been linked to the severe neurological disorder schizophrenia. This meta-analysis aimed to determine the association of T. gondii in schizophrenic patients and to explore sex as a potential confounding factor. Utilizing data from 36 eligible studies obtained from reputable databases, including PubMed, ScienceDirect, Research Gate, NCBI, and CENTRAL, 28 articles reported a significant association (p1) of schizophrenia among T. gondii-infected individuals. This suggests that T. gondii is a risk factor for schizophrenia. Subsequently, the study fails to reject the null hypothesis regarding sex as a confounding factor: (1) no significant association was observed between sex and T. gondii, and (2) only two studies obtained statistically significant results (pT. gondii infection and schizophrenia is not influenced by sex-related factors. Various mechanisms linking T. gondii infection to schizophrenia have already been explored, including its impact on glial cells, neurotransmitters, dopamine synthesis, and NMDAR autoantibodies. However, provided that there is still insufficient information on the confounders for T. gondii and schizophrenia, future studies could incorporate the role of culture, age, area of residence, eating habits, and pet ownership in their investigation.